Comparative study of voltage reference circuit for two stage amplifier / Ahmad Farhan Mhd Amin Nordin - Mhd Amin Nordin, Ahmad Farhan (2013)
The essence of this proposal is about a comparative study of voltage reference circuit for a two stage amplifier. In this proposal, the study is about a comparing voltage reference in two type of reference circuit used in a two stage amplifier. The research will focused on the parameters or characteristics between the references circuits to differentiate their precision and stability. Band gap reference circuits is a temperature independent voltage reference circuit while Bootstraps circuit is an arrangements of components used to boost the input impedance of a circuit by using a small amount of positive feedback. In this study, we will compare this two reference circuit characteristics and its output. The outcome of this research is to compare and analyze the voltage reference circuit on the two stage amplifier.